UMP students continue their studies online, postpone entering campus - Mimi Rabita, Abdul Wahit (2020)
Pekan, 5 October 2020 - Concerned about the current situation with the increase in positive COVID-19 cases in the country, Universiti Malaysia Pahang (UMP) has announced the postponement of all new and senior students who are scheduled to register at both UMP Pekan and Gambang campuses starting this October.